Herbs and Spices (IntechOpen, 2025)
Discover the powerful world of herbs and spices in this guide that bridges the gap between ancient traditions and modern science. Herbs and Spices - New Perspectives in Human Health and Food Industry unveils the secrets behind these botanical wonders and their profound impact on health and the food industry. Read about the medicinal properties of herbs and spices, supported by contemporary scientific research. From the anti-inflammatory effects of turmeric to the antioxidant properties of cloves, this book provides valuable insights into how these natural substances can enhance your health and well-being. Understand the role herbs and spices play in the food industry, from natural preservatives to functional foods. Explore trends in sustainability, clean labeling, and the growing demand for natural ingredients.